"Our Prosperity Rests Upon Manufactures": Industry in the Central Canadian Urban System, 1871 - Bloomfield, G.; Bloomfield, Elizabeth (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1994)
How urban was industrial activity in 1871, when only one in five Canadians lived in incorporated cities, towns or villages? This paper explores central Canada's urban-industrial system at a time of transition in industrial technology, business organization and work discipline. Based on analysis of the manuscript schedules of the First Census of Canada made machine-readable by the CANIND71 project, the article has three main parts. First, the whole urban-industrial system is described, using a classification that combines measures of the significance of industrial work in each place and of specialization in particular sectors with the population size of urban centres. Next, a typology of industrial workplaces is presented, combining measures of the number of workers with the extent to which non-manual power was used in the industrial process. Patterns of industry within urban places (especially Trois-Rivières and Guelph) are examined in order to assess factors such as rail and water transport, types of power, scale of process and size of output, and types of workplace and workforce. The authors propose questions and directions for further research on industry in Canada's urban centres.